Analisis Anteseden dari Innovative Work Behavior Pada Tenaga Kependidikan - Yoppi Syahrial; Indri Sri Endarwati (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This study uses the Cognitive Evaluation Theory which aims to examine the effect of inclusive leadership on innovative work behavior mediated by psychological empowerment. This study involved 229 educational staff spread across several cities in Indonesia using the convenience sampling method. The results in this study show that inclusive leadership and psychological empowerment are able to provide a positive and significant influence on innovative work behavior so that psychological empowerment is able to mediate the effect of inclusive leadership on innovative work behavior.